Analysis of the p53 gene and papillomavirus detection in smears from cervical lesions - Oliveira, Ledy do Horto dos Santos (2002)
CONTEXT: Alteration soft he p53 tumor suppressor gene are correlated with acritical step in the development of many human cancers.The tumor suppressor gene functions include regulation of the cell cycle and the cellular response to DNA damage, initiation of DNA repair and replication, induction of apoptosis and promotion of cell differentiation. CASE REPORT: Smears from ten cases of cervical lesions were analyzed for status of exons 5-8 of the p53 gene using PCR/SSCP. HPV infection was also screened by the PCR method using two PCR primer sets. Changes in the p53 gene were observed in a case of squamous carcinoma and a case of asymptomatic cervical intraepithelial neoplasia grade III (CIN III). High-risk HPV was detected in both cases showing that HPV infection and p53 mutation are not exclusive events.